Applied architecture patterns on the Microsoft platform : work with various Microsoft technologies using applied architecture patterns /: work with various Microsoft technologies using applied architecture patterns. (2014) - Dovgal, Andre; Noriskin, Gregor; Olechko, Dmitri
No abstract available